2020
DOI: 10.1101/2020.06.25.171975
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Increased Expression of Chondroitin Sulfotransferases following AngII may Contribute to Pathophysiology Underlying Covid-19 Respiratory Failure: Impact may be Exacerbated by Decline in Arylsulfatase B Activity

Abstract: The spike protein of SARS-CoV-2 binds to respiratory epithelium through the ACE2 receptor, an endogenous receptor for Angiotensin II (AngII). The mechanisms by which this viral infection leads to hypoxia and respiratory failure have not yet been elucidated. Interactions between the sulfated glycosaminoglycans heparin and heparan sulfate and the SARS-CoV-2 spike glycoprotein have been identified as participating in viral adherence and infectivity. In this brief report, we present data indicating that stimulatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 42 publications
(95 reference statements)
0
6
0
Order By: Relevance
“…Adjacent to the ACE2-binding site and exposed in the RBD lies a group of positively charged AA residues 129 that represents a potential site that could interact with HS, thus enhancing infectivity. 6,47,130 SARS-CoV-1 SP RBD did not show the same electropositive surface. 40 SARS-CoV-2 has approximately 10-20 times higher affinity for ACE2 than SARS-CoV-1, which could explain the higher infectivity rate of SARS-CoV-2.…”
Section: Cov-2 Cellular Entrymentioning
confidence: 79%
See 4 more Smart Citations
“…Adjacent to the ACE2-binding site and exposed in the RBD lies a group of positively charged AA residues 129 that represents a potential site that could interact with HS, thus enhancing infectivity. 6,47,130 SARS-CoV-1 SP RBD did not show the same electropositive surface. 40 SARS-CoV-2 has approximately 10-20 times higher affinity for ACE2 than SARS-CoV-1, which could explain the higher infectivity rate of SARS-CoV-2.…”
Section: Cov-2 Cellular Entrymentioning
confidence: 79%
“…Clausen et al and Kim et al found that the ectodomain of SARS‐CoV‐2 SP interacts with cell surface HS through RBD in the S1 subunit, 6,7 in a length‐ and sequence‐dependent manner 7,8,47 . The binding of HS to SARS‐CoV‐2 SP shifts the structure to favor the RBD open conformation that binds ACE2 receptors, 128 probably due to the release of furin by the GL after HS binding 3 .…”
Section: Pathogenesis Of Covid‐19mentioning
confidence: 99%
See 3 more Smart Citations